Leiomyosarcoma of the right ventricle extending into the pulmonary trunk. Issue 1 (1st July 2001) - Willaert, W; Claessens, P; Vanderheyden, M
Abstract : Primary leiomyosarcomas of the heart, particularly those affecting the right ventricle, are uncommon. A 70 year old woman presenting with the symptoms of progressive exertional dyspnoea and left sided pleuritic pain is presented. A leiomyosarcoma was diagnosed that originated in the right lateral ventricle wall, causing pulmonary outflow obstruction. Pathological analysis showed a neoplasm with a myxoid stroma, high mitotic activity, and nuclei expressing atypia. Immunohistochemical staining was found positive for vimentin and desmin. Seven months after complete surgical resection the tumour relapsed. This case illustrates the poor outcome, high relapse rate, and inefficiency of treatment associated with primary cardiac leiomyosarcomas. The current literature regarding incidence, diagnostic techniques, treatment strategies, and survival rates of this rare but terminal disease is reviewed.